2015
DOI: 10.1523/jneurosci.0956-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Anti-Hebbian LTP in CA1 Stratum Oriens Interneurons: Interactions between Group I Metabotropic Glutamate Receptors and M1 Muscarinic Receptors

Abstract: An anti-Hebbian form of LTP is observed at excitatory synapses made with some hippocampal interneurons. LTP induction is facilitated when postsynaptic interneurons are hyperpolarized, presumably because Ca 2ϩ entry through Ca 2ϩ -permeable glutamate receptors is enhanced. The contribution of modulatory transmitters to anti-Hebbian LTP induction remains to be established. Activation of group I metabotropic receptors (mGluRs) is required for anti-Hebbian LTP induction in interneurons with cell bodies in the CA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 82 publications
(55 reference statements)
2
31
0
Order By: Relevance
“…Synaptic potentiation can also be induced by a low concentration of the group I mGluR agonist DHPG, paired with hyperpolarizing current injection via the recording pipette (Le Duigou & Kullmann, ; Le Duigou et al . ). In control experiments, perfusion of DHPG (5 μ m ) paired with hyperpolarization for 10 min was followed by a large increase in EPSP slope ( n = 4) (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Synaptic potentiation can also be induced by a low concentration of the group I mGluR agonist DHPG, paired with hyperpolarizing current injection via the recording pipette (Le Duigou & Kullmann, ; Le Duigou et al . ). In control experiments, perfusion of DHPG (5 μ m ) paired with hyperpolarization for 10 min was followed by a large increase in EPSP slope ( n = 4) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…An unexplained finding is that exogenous activation of group I mGluRs with the selective agonist dihydroxyphenylglycine (DHPG) can be sufficient to induce LTP in the absence of presynaptic stimulation, when paired with postsynaptic hyperpolarization (Le Duigou & Kullmann, 2011;Le Duigou et al 2015). We recently reported that LTP can also be elicited when recording from regularspiking oriens-alveus (O/A) interneurons in the whole-cell configuration of the patch clamp method, with polyamines omitted from the pipette solution to relieve voltage-dependent blockade of CP-AMPARs (Nicholson & Kullmann, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is also convincing evidence that Grm5, together with kainite receptors, is involved in the mechanism of anti-Hebbian (AMPA/NMDA-independent) LTP formation in mossy fibers [ 27 ]. Moreover, it has been shown that activation of Grm1 and Grm5 is required for induction of anti-Hebbian LTP in hippocampal interneurons [ 28 ] and that the disruption of Grm5 signaling is associated with several disorders such as autism, depression and movement disorders [ 29 31 ]. However, the animals used in our studies demonstrated no hallmarks of neurological disorders.…”
Section: Resultsmentioning
confidence: 99%
“…M1Rs and mGluR1 have been shown to act synergistically within CA1 pyramidal cells to regulate intrinsic excitability via regulation of R-type Ca 2+ channels ( Park and Spruston, 2012 ) and both M1Rs ( Kim et al, 2002 ) and mGluR1 ( Morishita et al, 1998 ) can facilitate the release of endocannabinoids from CA1 pyramidal cells to cause depolarization induced suppression of inhibition. Furthermore, M1Rs and Group 1 mGluRs act in tandem to promote non-Hebbian LTP at glutamatergic synapses on CA1 interneurons ( Le Duigou et al, 2015 ). Interestingly, it has also been suggested that M1Rs and mGluR1 act selectively in functionally and anatomically distinct types of CA1 pyramidal cells to regulate plasticity of intrinsic excitability ( Graves et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%